1982
DOI: 10.1073/pnas.79.12.3739
|View full text |Cite
|
Sign up to set email alerts
|

Covalent crosslinking of angiotensin II to its binding sites in rat adrenal membranes.

Abstract: To identify the molecular components of the angiotensin II (All) receptor in the adrenal cortex, we have covalently linked "~I-labeled All ("MI-All) to its binding sites by using the chemical crosslinker disuccinimidyl suberate. Membrane fractions from rat adrenal tissue were incubated with "MI-All, washed, and treated with disuccinimidyl suberate. NaDodSO4/polyacrylamide gel electrophoresis carried out under reducing conditions followed by autoradiography showed that a major polypeptide(s) with an average Mr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…Previously, AT 1 receptor dimerization has been suggested by using various approaches. 1) Using Angiotensin affinity labeling, or chemical cross-linking experiments, AT 1 receptor complexes with a molecular weight corresponding to a dimeric complex have been identified in transfected cell lines and in several organs such as liver adrenal pituitary and brain (41)(42)(43)(44)(45). 2) High affinity ligand binding has been reconstituted by co-expression of two receptors (AT 1 -K102A and -K199A) that did not bind ligand when expressed individually (17).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, AT 1 receptor dimerization has been suggested by using various approaches. 1) Using Angiotensin affinity labeling, or chemical cross-linking experiments, AT 1 receptor complexes with a molecular weight corresponding to a dimeric complex have been identified in transfected cell lines and in several organs such as liver adrenal pituitary and brain (41)(42)(43)(44)(45). 2) High affinity ligand binding has been reconstituted by co-expression of two receptors (AT 1 -K102A and -K199A) that did not bind ligand when expressed individually (17).…”
Section: Discussionmentioning
confidence: 99%
“…The first *Correspondence: kjell.fuxe@ki.se doi: 10.7243/2052-6946-2-6 observations indicating the existence of homodimerization of GPCR were made in 1982 [9,10]. In 1987 homodimerization was found to take place upon epidermal growth factor (EGF) induced stimulation of the epidermal growth hormone receptor [11].…”
Section: Introductionmentioning
confidence: 99%
“…These analyses showed that is was possible to identify AT1R receptor complexes with molecular weights corresponding to both a monomeric and a dimeric form of the receptor. However, these observations were not linked to any functional consequences, and it has been speculated, that the dimers could result from technical artefacts causing protein aggregation (9,23,(49)(50)(51)(52)(53).…”
Section: At1 Receptor Activation and Signallingmentioning
confidence: 99%